Inter-Regional Variability in the Incidence of Skin and Subcutaneous Tissue Diseases of Children Aged 0-14 Years in the Russian Federation (а Population-Based Study) - Eleonora I. Pilguy; Leyla S. Namazova-Baranova; Igor A. Gundarov (Union of pediatricians of Russia, 2018)
Background. An effective system for management of pediatric dermatological care in Russia requires taking into account the peculiarities of regional morbidity. According to modern literature, this issue is not sufficiently developed. Our aim was to study the characteristics of variability in the incidence of skin and subcutaneous tissue diseases of children aged 0-14 years in the Russian Federation. Methods. The data of the state medical statistics on 83 territorial entities of the Russian Federation for 2009-2015 was used. The analysis implemented the risk aggregation method. The degree of variability in regional morbidity was assessed by the range of variation and the coefficient of variation. Region rankings were carried out by the annual incidence. The Spearman's rank correlation coefficient was used to study the stability of regions belonging to a certain ranked place. Results. In 2009, the incidence of skin and subcutaneous tissue diseases of children aged 0-14 years in the Russian Federation had a pronounced variability: the range of variation was 7.7 times, the coefficient of variation was 28%. The annual region rankings were carried out. In 2010-2015, the annual variability indices remained high. The coefficients of rank correlation when distributing regions by morbidity were in the range of 0.75-0.94 compared to 2009. Quintiles of regions with different levels of pediatric dermatological morbidity were singled out. Conclusion. The incidence of skin and subcutaneous tissue diseases in children aged 0-14 years in the territorial entities of the Russian Federation during 2009-2015 had a pronounced variability. Regions had a stable preference for a certain ranking place. The division of territorial entities of the Russian Federation into groups of pediatric dermatological morbidity are presented.